Crosstalk between hypoxic cellular micro-environment and the immune system: a potential therapeutic target for infectious diseases - Akinsulie, Olalekan Chris; Shahzad, Sammuel; Ogunleye, Seto Charles; Oladapo, Ifeoluwa Peace; Joshi, Melina; Ugwu, Charles Egede; Gbadegoye, Joy Olaoluwa; Hassan, Fasilat Oluwakemi; Adeleke, Richard; Afolabi Akande, Qudus; Adesola, Ridwan Olamilekan (Frontiers in Immunology, 2023)
There are overwhelming reports on the promotional effect of hypoxia on the malignant behavior of various forms of cancer cells. This has been proposed and tested exhaustively in the light of cancer immunotherapy. However, there could be more interesting functions of a hypoxic cellular microenvironment than malignancy. There is a highly intricate crosstalk between hypoxia inducible factor (HIF), a transcriptional factor produced during hypoxia, and nuclear factor kappa B (NF-κB) which has been well characterized in various immune cell types. This important crosstalk shares common activating and inhibitory stimuli, regulators, and molecular targets. Impaired hydroxylase activity contributes to the activation of HIFs. Inflammatory ligands activate NF-κB activity, which leads to the expression of inflammatory and anti-apoptotic genes. The eventual sequelae of the interaction between these two molecular players in immune cells, either bolstering or abrogating functions, is largely cell-type dependent. Importantly, this holds promise for interesting therapeutic interventions against several infectious diseases, as some HIF agonists have helped prevent immune-related diseases. Hypoxia and inflammation are common features of infectious diseases. Here, we highlighted the role of this cross-talk in the light of functional immunity against infection and inflammation, with special focus on various innate and adaptive immune cells. Particularly, we discussed the bidirectional effects of this crosstalk in the regulation of immune responses by monocytes/macrophages, dendritic cells, neutrophils, B cells, and T cells. We believe an advanced understanding of the interplay between HIFs and NF-kB could reveal novel therapeutic targets for various infectious diseases with limited treatment options.